Poly(l-Lactic Acid)/Gelatin Fibrous Scaffold Loaded with Simvastatin/Beta-Cyclodextrin-Modified Hydroxyapatite Inclusion Complex for Bone Tissue Regeneration - Lee, Jung Bok; Kim, Ji Eun; Balikov, Daniel A.; Bae, Min Soo; Heo, Dong Nyoung; Lee, Donghyun; Rim, Hyun Joon; Lee, Deok-Won; Sung, Hak-Joon; Kwon, Il Keun (Macromolecular bioscience, 2016)
Recently, the application of nanostructured materials in the field of tissue engineering has garnered attention to mediate treatment and regeneration of bone defects. In this study, poly(l‐lactic acid) (PLLA)/gelatin (PG) fibrous scaffolds are fabricated and β‐cyclodextrin (βCD) grafted nano‐hydroxyapatite (HAp) is coated onto the fibrous scaffold surface via an interaction between βCD and adamantane. Simvastatin (SIM), which is known to promote osteoblast viability and differentiation, is loaded into the remaining βCD. The specimen morphologies are characterized by scanning electron microscopy. The release profile of SIM from the drug loaded scaffold is also evaluated. In vitro proliferation and osteogenic differentiation of human adipose derived stem cells on SIM/HAp coated PG composite scaffolds is characterized by alkaline phosphatase (ALP) activity, mineralization (Alizarin Red S staining), and real time Polymerase chain reaction (PCR). The scaffolds are then implanted into rabbit calvarial defects and analyzed by microcomputed tomography for bone formation after four and eight weeks. These results demonstrate that SIM loaded PLLA/gelatin/HAp‐(βCD) scaffolds promote significantly higher ALP activity, mineralization, osteogenic gene expression, and bone regeneration than control scaffolds. This suggests the potential application of this material toward bone tissue engineering. β‐Cyclodextrin grafted hydroxyapatite nanoparticles are coated onto the surface of PLLA/gelatin fibrous scaffolds by an inclusion complex system. To provide a favorable microenvironment for bone tissue regeneration, simvastatin, an osteoinductive drug, is loaded into β‐cyclodextrin within the hydroxyapatite nanoparticle.